Beyond setting conservation targets: Q-method as a powerful tool to collectively set an action plan agenda - Levesque, Ann; Fouqueray, Timothée; Dupras, Jérôme (Frontiers in Conservation Science, 2023)
Nature conservation begins with detailed knowledge of the ecosystem based on inventories and maps. A difficult part of the conservation process subsequently starts, namely, the design of an action plan that achieves the desired protection outcome. As both funding and time are limited, conservation is subject to difficult trade-offs among competing land uses. We present a novel approach based on the Q-method to support local stakeholders that go beyond its usual use in assisting decision-making. We suggest a new usage of the Q-method: a tool to support conservation action prioritization. Our results indicate that the Q-method has valuable attributes, as (1) it encourages individual reflection on one’s own priorities; (2) it identifies different prioritization patterns among respondents; (3) it provides input to later collective discussions, ultimately contributing to establishing consensus; (4) it brings additional arguments to conservation planners based on the latter’s declared priorities. Overall, this use of Q-method can help stakeholders prioritize conservation actions, a crucial step toward achieving ecologically and socially robust conservation action plan.